Toward urban environmental sustainability: The carbon footprint of Foggia's municipality. (10th June 2018) - Lombardi, Mariarosaria; Laiola, Elisabetta; Tricase, Caterina; Rana, Roberto
Abstract: Cities are mainly responsible for greenhouse gas (GHG) emissions in the atmosphere and thus for climate change. The European Union (EU) set up a series of strategies and policies to facilitate the elaboration of climate change mitigation and adaptation of urban plans. To do this, it is necessary to measure the city's GHG emission level. The Urban Carbon Footprint (UCF) and its derivation, the Relative Carbon Footprint (RCF), represent the most appropriate tools for obtaining this important information. The present paper applies these indicators to a small city (150 000 inhabitants) located in Southern Italy, a novelty for academic studies, which usually concentrate on megacities. The study focuses only on CO2 emissions, as these represent 90% of the total GHGs released in urban areas. The findings showed that in 2015 the total UCF was equal to 288 ktCO2, specifically deriving from electricity and natural gas consumption. Moreover, Residential, Industry and Tertiary are the most carbon-intensive economic sectors. The RCF was equal to 0.30; the city emission levels were lower than the national average. Therefore, the municipality represents a typical "net-consumer" community, dominated by homes with territorial emissions due to consumption and characterized by a low number of industries and an average income per capita that is 50% lower than the national one. Starting from these results, the study proposed an urban action plan according to the EU mitigation and adaptation policies. This plan could help the local government improve its environmental sustainability, even if more public city-level data is required for a more comprehensive analysis. Finally, it would be more appropriate for all actions to be aligned under a unique policy process to seize the opportunity to link the various local intervention policies from different fields, taking into account their existing funding, tools, processes, and resources. Capitalizing on the adaptation/mitigation connection will allow municipalities to leverage their climate change action efforts and accelerate progress toward their climate and energy goals. Highlights: UCF and RCF are tool for assessing the urban environmental sustainability. Foggia is a small city (150 000 inhabitants), a typical "net-consumer" community. UCF and RCF of Foggia's municipality was equal to 288 ktCO2 and 0.30 in 2015. UCF data was needed for defining a mitigation and adaptation action urban plan.